Effects of oxytetracycline and amoxicillin on development and biomarkers activities of zebrafish (Danio rerio) - Oliveira, Rhaul (2018)
Antibiotics have been widely used in human and veterinary medicine to treat or prevent diseases. Residues of antibiotics have been found in aquatic environments, but their effects on fish have been not properly investigated. This work aimed to assess the sub-lethal effects of oxytetracycline and amoxicillin on zebrafish development and biomarkers. Embryos and adults were exposed during 96. h to amoxicillin and oxytetracycline following OECD guidelines. Tissues of adults and pools of embryos were used for catalase, glutathione-S-transferases and lactate dehydrogenase determinations. Amoxicillin caused premature hatching (48h-EC50. =. 132.4. mg/l) whereas oxytetracycline cause delayed hatching of embryos (72h-EC50. =. 127.6. mg/l). Moreover, both antibiotics inhibited catalase and induced glutathione-S-transferases in zebrafish adults. However, only oxytetracycline induced lactate dehydrogenase. Short-term effects of antibiotics were observed at high doses (mg/l) indicating that physiological impairment in fish populations is unlike to occur. However, effects of chronic exposures to low doses of ABs must be investigated.